Assessment of injection safety practices among anesthesiologists in tertiary care hospitals in Karachi - Kumar, Ajeet; Ur Rehman, Adeel; Aziz, Tarique; Naeem, Kashif; Wanwari , Mahendar; Kumar, Harmit (International Journal of Endorsing Health Science Research, 2024)
Background: Injections play a critical role in the medical management of patients, particularly those with severe health conditions, across hospitals and healthcare institutions. However, ensuring adherence to proper injection safety protocols is essential to prevent avoidable medical errors and infections. The objective of this study was to evaluate the compliance with injection safety protocols among anesthesiologists working in tertiary care institutions in Karachi. Methodology: A cross-sectional study was conducted in tertiary care hospitals in Karachi between November 2021 and April 2022, with a study duration of six months. A total of 200 anesthesiologists participated in the study. Data were collected through a pre-designed questionnaire, which was completed by the participants. All responses were kept confidential to ensure anonymity. The study aimed to assess adherence to injection safety protocols among anesthesiologists working in these institutions. Results: Among the 200 anesthesiologists surveyed, 18.5% were found to engage in malpractice regarding injection safety practices, while the remaining 81.5% adhered to acceptable injection safety protocols. Statistical analyses were performed to explore the relationship between age, years of experience, and other demographic factors, revealing no significant differences between those following acceptable practices and those engaging in malpractice. Conclusion: The study concludes that enhancing awareness and providing training on injection safety for healthcare professionals can significantly improve compliance and reduce the incidence of needle-stick injuries. It is recommended that regular training sessions and updated safety protocols be implemented in all healthcare facilities to further minimize the risks associated with unsafe injection practices.